Effects of Primary Health Care Staff Training on Maternal and Child Health Services - sana mutlaq al dafiry Munera Raja al dafiry Saada Awad Al-Matrafiy Salem Mater al dafiry Meshal Defallah al dafiry (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The training of primary health care (PHC) staff is part of a national initiative aimed at enhancing the capabilities of PHC personnel . Initiated in the year 1444H, the program’s primary goal is to equip all PHC staff, including doctors, nurses, and midwives, with the necessary skills to provide comprehensive Maternal and Child Health (MCH) services. By the end of 1445H, this objective was successfully realized